The textuality of diagonal ornamentation: Historical transformations of signification from the Baltic perspective. - Tumėnas, Vytautas (Sign Systems Studies, 2014)
This paper deals with textual aspects of the geometric diagonal linear ornamentation that appears on traditional woven Lithuanian bands. Taking into consideration diachronic, local as well as universal perspectives, it aims to determine and classify the basic elements of the ornament that relate to the development of textuality. Previous investigations of Baltic and Lithuanian textile ornaments have been based on a purely geometric analysis of ornamental form, or on creating linguistic inventories of folk pattern denominations. This paper describes a unique, elaborated, interdisciplinary method for studying such ornaments based on historical-typological comparative analyses, the classification of patterns with regard to their form and meaning, and the semiotic interpretation of mythopoetic images of patterns names. Further, the paper discusses whether an authentic folk classification and a tradition of typology based on the forms of patterns and names can be detected. From the traditional point of view the main meaning-carrying element of this ornamentation is the type of pattern. Therefore, reconstructions and interpretations of the semantic field of patterns' signification may be based on the mythopoetic context of folk culture.